(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article talks about the rapid development of tourism in Kashkadarya region and the role of Karshi in these processes. Also, detailed information is given about the shrines and architectural monuments located in the city. The article also provides information about the possibilities of tourism development and new tourist destinations.